Revamping of Public Health Surveillance System in India - Manisha Wadhwa (Columbia University, Earth Institute, Center for Sustainable Development (CSD), 2021)
Traditionally, India has focused on surveillance of communicable/infectious diseases such as small pox, polio, malaria etc., and the Integrated Disease Surveillance Programme (IDSP), with assistance from state governments, has played a key role in tracking and tracing these diseases. Sustainable progress has been achieved such as smallpox eradication in 1977, polio elimination in 2014 and reduction in the incidence of malaria. However, now the scope of tracking other diseases such as non-communicable diseases(NCDs) like diabetes, hypertension etc. and other emerging/ re-emerging diseases is being increased. Newer surveillance techniques such as participatory disease surveillance (PDS) have emerged. The surveillance system in India has so far evolved in conducting surveillance within the domains of human health, animal health, and the environment, but in silos. Public Health Surveillance is often viewed as a stand-alone activity, but in reality it cuts across all levels of care-primary, secondary and tertiary and many institutions are involved at different aspects. The ongoing COVID-19 pandemic has emphasized the need to build a robust, unified disease surveillance system in the country that cuts across all the relevant sectors to deal with the disease holistically. It is envisioned that public health surveillance in 2035 would be based on a Single Surveillance Information System that would collate information from various sources such as national programs like Integrated Disease Surveillance Program (IDSP), National AIDS Control Program (NACP) and National Tuberculosis Elimination Program (NTEP), hospitals and health centres, health insurance records, laboratories, pharmacies, plant and animal disease surveillance, environmental health surveillance, occupational health & injury surveillance etc. The creation of unified e-health records via use of unique health identity number (UHID), as recommended by the National Digital Health Bueprint, forms the foundation for the future of public health surveillance in India.
Keywords: 330; Public Health Surveillance; India